Ice age. Continental drift [videorecording (DVD)] - Martino, Steve, 1959-; Thurmeier, Mike; Romano, Ray; Leguizamo, John; Leary, Denis; Scott, Seann William; Peck, Josh, 1986-; Dinklage, Peter; Sykes, Wanda, 1964-; Lopez, Jennifer, 1970-; Queen Latifah, 1970-; Gad, Josh, 1981-; et al. (20th Century Fox Home Entertainment, 2012)
Scrat's constant quest for an acorn causes a shift in the ice. Manny, Sid, and Diego end up stranded on an iceberg in the middle of the sea. A group of misfit pirates are determined to stop the trio from ever returning home.